Intracerebral hematoma after evacuation of chronic subdural hematoma Intrazerebrales Hämatom nach Entleerung eines chronischen subduralen Hämatoms - Övül, I.; Öner, K. (Neurochirurgia, 1988)
A case of intracerebral hemorrhage occurring after evacuation of a chronic subdural hematoma is presented. The mechanism of this complication is not clear. However, hemorrhage into previously undetected areas of contusion, damage to cerebral vasculature secondary to rapid perioperative parenchymal shift, and sudden increase in cerebral blood flow with focal disruption of autoregulation have been postulated as causes. Although this is a rare complication after decompressive operation for chronic subdural hematoma, it should be suspected and investigated without delay in patients who deteriorate postoperatively.Es wird über eine intrazerebrale Blutung, die nach der Entfernung eines subduralen Hämatoms entstanden ist, berichtet. Der Mechanismus dieser Komplikation ist nicht klar. Es werden jedoch als mögliche Ursachen die Blutung in einen unbekannt gebliebenen Kontusionsherd, die Schädigung zerebraler Gefäße als Folge einer Parenchymverlagerung während der Operation, und plötzlicher Anstieg des zerebralen CBF mit fokaler Unterbrechung der Autoregulation angenommen. Obwohl diese Komplikationen nach Entlastungsoperationen wegen chronischen subduralen Hämatoms selten sind, sollte bei Patienten mit postoperativer Desorientierung diese Möglichkeit frühzeitig vermutet und festgestellt werden.
Keywords: Subdural hematoma; Intracerebral hemorrhage; Head injury